Dark Matter of Learning: A Virtual Ethnography of Digital Underground Communities and the Socio-Emotional Infrastructure of Student Learning - Ian Harum Prasasti; Donny muda priyangan; Arif Rohman Hakim; Alifiatun Asyifah (Publikasi Indonesia, 2026)
A Digital learning does not take place exclusively within formal platforms such as Learning Management Systems (LMS), but also emerges in informal and often invisible digital spaces beyond institutional control. This study examines how informal student WhatsApp communities function as a socio-emotional infrastructure that supports learning processes outside formal educational systems. Employing a qualitative virtual ethnography approach, data were collected through passive observation, digital documentation, and analysis of naturally occurring conversations and shared learning artefacts over one academic semester. Thematic analysis following Braun and Clarke’s framework identified four interconnected themes: collaborative learning management, access and distribution of academic knowledge, emotional support and peer solidarity, and safe spaces for academic courage. The findings reveal that these informal digital communities operate as an alternative learning ecosystem that sustains students’ academic engagement, emotional well-being, and willingness to participate intellectually. This study conceptualizes such communities as the “dark matter of learning” an invisible yet critical socio-emotional structure that underpins student learning beyond institutional LMS environments. The findings highlight the importance of recognizing and integrating informal digital learning spaces into a more holistic digital learning ecosystem.